Experience with luspatercept therapy in patients with transfusion-dependent low-risk myelodysplastic syndromes in real-world clinical practice: exploring the positive effect of combination with erythropoietin alfa - Jonasova, Anna; Sotakova, Slavka; Belohlavkova, Petra; Minarik, Lubomir; Stopka, Tomas; Jonas, Jan Jakub; Aghova, Tatiana; Zemanova, Zuzana (Frontiers in Oncology, 2024)
Background Luspatercept, an inhibitor of the transforming growth factor beta (TGF-β) pathway, is a novel treatment for anemic patients with lower-risk myelodysplastic syndromes (MDS) with transfusion dependence (TD) who do not respond to erythropoiesis-stimulating agents (ESA) therapy or are not suitable candidates for this treatment. We present real-world experience with luspatercept therapy from two hematology centers in the Czech Republic. Methods By January 2024, 54 MDS patients (33 men, 21 women) with a median age of 74 years (range, 55–95) were treated with luspatercept ± ESA at two Charles University hematology centers in Prague and Hradec Králové. According to the WHO 2016 classification, the cohort included 32 MDS-RS-MLD, seven MDS-MLD, two patients with 5q- + ring sideroblasts (RS), 12 RARS-T, and 1 patient with CMML-0 + RS. SF3B1 mutation data were available for 45 patients. All patients were in the IPSS-R and IPSS-M lower-risk groups (except four IPSS-M high). The median follow-up was 17 months (range, 1–54). All patients were transfusion-dependent. Thirty-five (64.8%) patients had a high transfusion burden (HTB) with ≥ 4 transfusion units (TU)/8 weeks, and 19 (35.2%) had a low transfusion burden (LTB) (< 4 TU/8 weeks). The median time between diagnosis and initiation of luspatercept was 27 months (range, 4–156). ESA were used prior to luspatercept in 45 patients, and luspatercept was used as first-line treatment in nine patients. Thirty-one (61%) patients were treated simultaneously with ESA. Results Only patients who received luspatercept for ≥ 8 weeks (51 patients) were assessed. We evaluated the achievement of transfusion independence (TI) lasting 8, 12, 16, and 24 weeks. Thirty-two (62.7%) patients achieved TI for ≥ 8 weeks, 31 (60.7%) for ≥ 12 weeks, 29 (56.8%) for ≥ 16 weeks, and 25 (49%) for ≥ 24 weeks. Hematologic improvement (HI) without TI was achieved in six patients (11.7%). Overall, HI + TI was achieved in 38 patients (74.5%). Epoetin alfa was used simultaneously in 31 patients (60.7%). In 21 (55.2%) of all responding patients, concomitant therapy with epoetin alfa led to an improved response, with 16 reaching TI. Thirteen (25.5%) patients were nonresponders. Eight (21%) patients experienced therapy failure and became transfusion-dependent again. Optimal response required a gradual increase in the luspatercept dose to 1.75 mg/kg in up to 35 patients, with 23 responders (TI + HI). Response rates varied by transfusion burden: 79% in LTB and 50% in HTB reached TI. Of RS+ patients, 70% reached TI, while only one out of five RS− patients achieved TI. Among 39 SF3B1-positive patients, 61.6% achieved TI. In the low and very low IPSS-M groups, 86% of patients responded (TI + HI), compared to 62% in the moderate-low group. Luspatercept was well-tolerated, with no adverse events higher than grade II toxicity. Conclusion We have demonstrated in real-world clinical practice that luspatercept is a very effective agent, even in an unselected, pretreated, significantly TD MDS population. The effect was particularly high in the IPSS-M low and very low groups. We believe that the relatively high response rate in our patients was influenced by the frequent use of a higher dose (1.75 mg/kg) and especially by adding ESA to luspatercept in poorly responding patients.